(untitled) (Jurnal Teknologi Industri Pertanian, 2023)
Consumers have an important role in the sustainability of a business. Producers who can meet the needs and desires of consumers have a competitive attitude and will continue to survive. The involvement of consumers as early as possible in product design can increase the suitability between the products produced and the needs of consumers as users. This study aims to design the development of processed-grasshopper products in the form of snack bars as local food wisdom in Gunungkidul Regency, DIY according to consumer preferences. The method used in this research is Quality Function Deployment (QFD). Data were collected using a questionnaire on consumers of grasshopper-processed products in Gunungkidul Regency, DIY. The method of sampling was using a purposive sampling method. The results showed that in the development of grasshopper snack bar products, four technical parameters that had a weight value of more than 10% were the type of main raw material, protein content, mixed grasshopper flour content, and dough cutting size. The four technical parameters have a total weight point of 54% which can be developed to satisfy consumers. The availability of quality raw materials (fresh and containing high protein) is the main aspect that needs to be considered so that grasshopper processed products in the form of snack bars can fulfill consumer demands also become new superior products that can support the image of gastro tourism in Gunungkidul Regency. Keywords: grasshopper, Gunungkidul, quality function deployment (QFD), snack bar